The Relationship Between Ownership Structure, Capital Structure, and Firm Performance: The Evidence From Indonesian Manufacturing Sector - Candy, Candy; Quinn, Fionna (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
The manufacturing sector listed on the Indonesia Stock Exchange (IDX) has experienced a decline in performance that could be attributed to its ownership structure. Besides, Indonesian manufacturing companies rank highly among foreign debt borrowers, with a total debt of US 392.6 billion, as reported by Bank Indonesia's Foreign Debt Statistics (SULNI) emphasizing the importance of analyzing their capital structure to understand their financial health, as it is influenced by their debt and capital holdings. This study aims to thoroughly examine the pivotal roles of ownership structure and capital structure in shaping the future trajectory of companies in Indonesia's manufacturing sector, with a specific focus on how their financial decision-making affects their performance. This study analyzed data from 97 listed companies on the IDX over five years (2017-2021) using a statistical method called panel regression. The findings indicate that the way a company is owned does not significantly influence its performance. However, the study does uncover that capital structure, measured by DAR, negatively impacts ROA without affecting ROE. On the other hand, the capital structure measured by DER negatively impacts ROE without affecting ROA. Firm size plays a significant and positive role in influencing company performance as a control variable.